'A Warning Against Quack Doctors': the Old Bailey trial of Indian oculists, 1893*. Issue 231 (1st February 2012) - Mukherjee, Sumita
Abstract The cataract operation is said to have been perfected by Susruta, the 'Hippocrates of India', some time around the sixth century B.C.E. However, at the end of the nineteenth century in Britain, India's reputation for expertise in ocular surgery was under threat and at the point of being discredited. At this time, a number of Indian oculists were working in Britain, outside the professional medical sector using itinerant methods and forms of advertising that were associated with 'quacks'. The activities of four Indian eye‐doctors came to the fore with a trial at the Old Bailey in 1893 for 'fraud'. This article locates such Indian oculists within a tradition of 'fringe medicine' in Britain, and discusses, in particular, their methods of advertising and the proceedings of the aforementioned trial.